Jerusalem between the Inscription of Identity and Enhancement of Resistance in Mahmoud Darwish's Poetry - N. Mousa, Ibrahim (Anaquel de Estudios Árabes, 2011)
This study sheds lights on the image of Jerusalem in Mahmoud Darwish’s Poetry from a stylistic perspective in two sections: the first concentrates on “ history and identity” phenomenon which has its deep roots in the Palestinian history and geography. This formed the National identity and the cultural being for the Palestinian as a response to the enemy’s attempts to confiscate the identity of the Palestinian Place. The second section reveals “occupation and resistence” the tragic Palestinian life represented in the occupation’s cruelty and displacement of a whole nation. However , this will not prevent the Palestinian from clinging to his right in defending his land and his Jerusalem since defending them is an obvious manifestation guarding of his memory and human existence.
Keywords: Mahmud Darwish´s Poetry; Jerusalem; Identity; Occupation; Resistance; Disaster.